ASPEK PERPAJAKAN PADA PERUSAHAAN E-COMMERCE PT.XYZ - Naomi Silvia, - (2019)
This study describes taxation of value added taxes and taxes on e-commerce companies PT. XYZ. The purpose of this study is to study how aspects of taxation in the e-commerce company PT. XYZ compare the existing taxation aspects in conventional which increases the potential of existing taxes. This study uses a descriptive qualitative method using phenomenology and interpretive paradigms. The object in this study is one of the foreign e-commerce companies, PT. XYZ. Ecommerce in Indonesia which has a digital platform in fact has not provided the potential and complete support for tax revenue. This is because there are still many e-commerce companies that have not yet accepted themselves as corporate taxpayers, as well as the number of e-commerce companies that have not met their tax requirements from the digital platforms needed. Thus, the role of the government, especially the Director General of Taxes, requested special supervision aimed at collecting tax potential from the e-commerce sector.